Perbandingan Regulasi Hukum Mengenai Perlindungan Data Pribadi terkait Penerapan Definiton of Specified Message dalam Sistem Transaksi E-Commerce antara Indonesia dengan Singapura - Siallagan, Kevin Josua; Shelly Kurniawan (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The field of technology, information and communication is currently growing rapidly, making it easier for people to make transactions. Currently, people are interested in doing shopping in E-Commerce. However, this is a special concern for the community and the government because crimes in E-Commerce transactions can occur at any time and it is very easy to do, such crimes include personal data leakage. With the increasing cases of personal data leakage today, this research article is prepared with the intention of evaluating the effectiveness of legal regulations currently in force and providing special guarantees for consumers related to legal protection. This research is examined through a comparative analysis between Law No. 27 of 2022 on Personal Data Protection and Personal Data Protection Act No.40 of 2020. In this research, it also discusses the application of ‘DO NOT CALL REGISTRY’ specifically the ‘Definition of Specified Message’ section to increase public awareness of the importance of using personal data in transactions. By conducting a legal comparison.